2022
DOI: 10.1186/s40168-022-01312-0
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of viral infection and subsequent antimicrobials on the microbiome-resistome of growing pigs

Abstract: Background Antimicrobials are used in food-producing animals for purposes of preventing, controlling, and/or treating infections. In swine, a major driver of antimicrobial use is porcine reproductive and respiratory syndrome (PRRS), which is caused by a virus that predisposes infected animals to secondary bacterial infections. Numerous antimicrobial protocols are used to treat PRRS, but we have little insight into how these treatment schemes impact antimicrobial resistance (AMR) dynamics within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 98 publications
1
11
0
Order By: Relevance
“…An age-related decline in phenotypic as well as genotypic (ARGs) quantity in fecal bacteria from pigs raised with or without antibiotics has been documented [ 11 , 16 , 67 ]. A recent study in wean-to-market pigs also showed that despite significant differences in the intensity of antibiotic exposures, resistome composition remained largely similar between those pigs that received minimal to moderate versus intensive antibiotic exposures [ 68 ]. Thus, overall reduction in the number of ARGs could well be due to age-related shifts in underlying microbial taxa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An age-related decline in phenotypic as well as genotypic (ARGs) quantity in fecal bacteria from pigs raised with or without antibiotics has been documented [ 11 , 16 , 67 ]. A recent study in wean-to-market pigs also showed that despite significant differences in the intensity of antibiotic exposures, resistome composition remained largely similar between those pigs that received minimal to moderate versus intensive antibiotic exposures [ 68 ]. Thus, overall reduction in the number of ARGs could well be due to age-related shifts in underlying microbial taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Factors other than antimicrobial exposure have been shown to be associated with AMR gene levels in the feces of pigs [ 82 ]. Additionally, events such as viral illness and physical grouping of pigs have been shown to influence the dynamics of the microbiome and resistome in pigs [ 68 ]. These findings, along with our own results, suggest that factors driving AMR require investigation beyond merely focusing on antimicrobial use [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, compared to the pasture-raised pigs, the abundance of ARGs within nearly all antimicrobial classes was significantly higher in the conventionally-raised pigs. These ARGs included many that are typically abundant in commercial pigs such as aph(3')-IIIa, cfxA2, erm(B), erm(F), lnu(C), tet (44), tet(Q), tet(W), and tet(X) [2,[47][48][49]. Some of these ARGs were also assembled and binned into specific MAGs thus providing taxonomic information.…”
Section: Discussionmentioning
confidence: 99%
“…Viral sequences were identified based on VirSorter2's SOP with (Guo et al, 2021b) and P>=0.95 using DeepVriFinder. We collected metagenomics data from various sources, including SRP188615/PRJNA526405 (Gaio et al, 2022;Gaio et al, 2021), CNP0000824 (Chen et al, 2021b), PRJEB11755 (Xiao et al, 2016), PRJNA788462 (Gaire et al, 2022), PRJNA775062 (Tao et al, 2022), PRJEB22062 (Luiken et al, 2020), PRJCA009609 (Wu et al, 2022a), PRJEB44118 (Zhang et al, 2022), and 70 samples collected in our lab. In total, 4,650 samples were used in our study to extract the viral contigs.…”
Section: Data Assembly and Viral Identificationmentioning
confidence: 99%
“…Several databases, such as GOV2 (Gregory et al, 2019), IMG/VR4 (Camargo et al, 2023a), GVD (Gregory et al, 2020), MGV (Nayfach et al, 2021b), and GPD (Camarillo-Guerrero et al, 2021), have been established to facilitate the analysis of virome from various environments using metagenomic data. Since the establishment of these databases, the number of publicly available pig gut microbiota datasets has rapidly increased (Chen et al, 2021b;Gaio et al, 2022;Gaio et al, 2021;Gaire et al, 2022;Luiken et al, 2020;Tao et al, 2022;Wu et al, 2022a;Xiao et al, 2016;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%